2019
DOI: 10.1186/s40478-019-0686-6
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiography validation of novel tau PET tracer [F-18]-MK-6240 on human postmortem brain tissue

Abstract: [F-18]-MK-6240, a novel tau positron emission tomography (PET) tracer recently discovered for the in vivo detection of neurofibrillary tangles, has the potential to improve diagnostic accuracy in the detection of Alzheimer disease. We have examined regional and substrate-specific binding patterns as well as possible off-target binding of this tracer on human brain tissue to advance towards its validation. We applied [F-18]-MK-6240 phosphor screen and high resolution autoradiography to postmortem samples from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 34 publications
12
113
1
1
Order By: Relevance
“…In autoradiography studies it also showed to tau aggregates/folds in PSP brain sections, which of course has been controversial, since many tau tracers has been reported not to be bind to tau deposits in PSP in autoradiography experiments. However, off-target binding was observed in the pars compacta portion of the substantia nigra in human brain sections, consistent with the affinity of some tau tracers like flortaucipir, [ 18 F]MK-6240 to melanin-containing cells [52,53,201].…”
Section: Optimized First Generation Tau Tracerssupporting
confidence: 68%
See 1 more Smart Citation
“…In autoradiography studies it also showed to tau aggregates/folds in PSP brain sections, which of course has been controversial, since many tau tracers has been reported not to be bind to tau deposits in PSP in autoradiography experiments. However, off-target binding was observed in the pars compacta portion of the substantia nigra in human brain sections, consistent with the affinity of some tau tracers like flortaucipir, [ 18 F]MK-6240 to melanin-containing cells [52,53,201].…”
Section: Optimized First Generation Tau Tracerssupporting
confidence: 68%
“…Preclinical findings confirmed a lack of binding to MAO-A and MAO-B [203]. Unlike flortaucipir and [ 18 F]THK-5351 off-target binding was not seen in the choroid plexus and basal ganglia [204], but like flortaucipir and various tau PET tracers, off-target binding to neuromelanin-and melanin containing cells like the pigmented neurons in the substantia nigra, and meninges was observed [52,187,201]. To confirm initial observations, there are ongoing clinical trials on non-AD patients.…”
Section: The Azaindole-isoquinoline and Naphthyridine Derivativesmentioning
confidence: 72%
“…To address this, we preselected an atlas that excludes these typical AV1451 off-target binding regions. Still, it is possible, that unspecific AV1451 binding may influence our results, hence our findings await further replication once second-generation tau-PET tracers with a better off-target binding profile are available 41,42 . Here, it will be of special interest to study the role of the hippocampus in connectivity-related tau-spreading, which is a site of early tau pathology that may be critically involved in tau spread from alloto the neocortical regions 43,44 .…”
Section: Discussionmentioning
confidence: 83%
“…This has resulted in overestimation of Tau. Recent in vitro studies with [ 18 F]MK‐6240 in AD brain suggests some displacement (up to 20% at high drug concentrations) and may not be a concern for in vivo PET studies (Aguero et al., 2019). Binding of [ 125 I]IPPI in brain slices containing AC and CC shown in Figure 8b correlated very well with the presence of Tau, confirmed by anti‐Tau Dako A0024 (Figure 8h).…”
Section: Discussionmentioning
confidence: 99%
“…As a NFT radiotracer, [ 18 F]MK‐6240 shows characteristic changes in the brains of patients with AD (Betthauser et al, 2019). More recently, using autoradiographic studies, [ 18 F]MK‐6240 has some propensity of being displaced by MAO inhibitors in vitro (Aguero et al., 2019).…”
Section: Introductionmentioning
confidence: 99%